Frontline Science: Coincidental null mutation of Csf2rα in a colony of PI3Kγ−/− mice causes alveolar macrophage deficiency and fatal respiratory viral infection. Issue 2 (28th July 2016) - Schneider, Christoph; Nobs, Samuel P.; Heer, Alex K.; Hirsch, Emilio; Penninger, Josef; Siggs, Owen M.; Kopf, Manfred
Abstract : PI3Ks have been identified as key signaling proteins involved in many basic biologic processes in health and disease. Transgenic animals have been essential tools to study the underlying molecular mechanisms in this context and therefore, have been widely used to elucidate the role of these factors in many different settings. More specifically, PI3Kγ, a subunit highly expressed in the hematopoietic system, has been implicated to play an important role in many inflammatory diseases as well as cancer. Here, we report identification of multiple, additional, previously unknown mutations in the genome of a widely used PI3Kγ‐deficient (PI3Kγ −/− ) mouse colony. These include a STOP mutation in the GM‐CSFRα chain, leading to a complete and specific deficiency in GM‐CSF signaling. PI3Kγ −/− animals consequently lacked alveolar macrophages (AMs) and succumbed rapidly to influenza virus infection. Furthermore, PI3Kγ −/− mice carried an additional mutation that affects mucin 2 (Muc2) transcripts. This protein is strongly involved in the regulation of colorectal cancer, and indeed, conflicting reports have indicated that PI3Kγ −/− animals spontaneously develop colorectal tumors. Thus, we uncover previously unknown, confounding factors present in a strain of PI3Kγ −/− mice, leading to additional deficiencies in important signaling pathways with potentially wide‐ranging implications for the interpretation of previous studies. By separating the mutations, we established a unique Csf2ra −/− mouse model that allows us to study the role of cell intrinsic GM‐CSFR signaling in vivo without confounding variables introduced by defective IL‐5R and IL‐3R signaling in mice lacking the common β chain (Csf2rb).